Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1034/j.1600-0404.2000.102005317.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient autonomic nervous system dysfunction during hyperacute stroke

Abstract: Forty-four patients suffering a stroke for the first time were examined within 10 h of the onset of symptoms; the tests performed on their admission to hospital, and thereafter on the third and seventh day, were 24-h Holter EKG with spectral analysis of heart rate variability, evaluation of arterial blood pressure and the levels of catecholamine in the blood and 24-h urine. The dynamic EKG on admission revealed that 31 (70.5%) out of the 44 patients already had arrhythmia. These alterations were observed in 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 0 publications
7
51
1
2
Order By: Relevance
“…[1][2][3][4] Abnormalities of cardiovascular autonomic control may also retain prognostic relevance, as reduced heart rate variability (HRV) and impaired cardiac baroreceptor sensitivity have both been associated with adverse clinical outcome after stroke. [5][6] Furthermore, all stroke-related autonomic abnormalities appear more relevant in patients with right-sided hemispheric infarctions, [7][8][9][10] with concurrent involvement of the right insula implying further derangement of cardiovascular function 10 -13 and even an increase of the odds of death within 3 months of acute stroke. 14 However, to date, the relative prognostic significance in stroke patients of right-sided insular involvement in the infarct area, as well as that of cardiac autonomic impairment and arrhythmias, has not been fully clarified.…”
mentioning
confidence: 99%
“…[1][2][3][4] Abnormalities of cardiovascular autonomic control may also retain prognostic relevance, as reduced heart rate variability (HRV) and impaired cardiac baroreceptor sensitivity have both been associated with adverse clinical outcome after stroke. [5][6] Furthermore, all stroke-related autonomic abnormalities appear more relevant in patients with right-sided hemispheric infarctions, [7][8][9][10] with concurrent involvement of the right insula implying further derangement of cardiovascular function 10 -13 and even an increase of the odds of death within 3 months of acute stroke. 14 However, to date, the relative prognostic significance in stroke patients of right-sided insular involvement in the infarct area, as well as that of cardiac autonomic impairment and arrhythmias, has not been fully clarified.…”
mentioning
confidence: 99%
“…In some studies there is an uncertainty if these changes are secondary to stroke, it is thought that stroke may affect cardiac rhythm directly or indirectly (20). It was reported that the incidence of ECG abnormality after acute ischemic stroke is between 45% and 90%.…”
Section: Discussionmentioning
confidence: 99%
“…{1} This is predicated on our observation of a specific association between visuospatial cognitive measures and mortality in non-demented elderly retirees. {2} Similar tests are known predict mortality in AD {3}, while right (R) hemisphere lesions are known to increase the risk of arrhythmic morbidity and mortality in stroke {4}, head injury {5} and epilepsy {6}. Strokes that affect constructional tasks often involve the R insula as well {7}.…”
Section: Introductionmentioning
confidence: 99%